2007
DOI: 10.1007/s10799-007-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Controlled experimentation on adaptations of pair programming

Abstract: The use of agile methods is growing in industrial practice due to the documented benefits of increased software quality, shared programmer expertise, and user satisfaction. These methods include pair programming (two programmers working side-by-side producing the code) and test-driven approaches (test cases written first to prepare for coding). In practice, software development organizations adapt agile methods to their environment. The purpose of this research is to understand better the impacts of adapting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…In others , students kept the same partner throughout the term unless unforeseen circumstances occurred. Domino et al (2007) reported better performance and satisfaction outcomes using face-to-face pair programming as compared to its virtual setting. They also found that limiting the extent of collaboration can be effective, especially when programmers are more experienced.…”
Section: Literature Reviewmentioning
confidence: 98%
See 1 more Smart Citation
“…In others , students kept the same partner throughout the term unless unforeseen circumstances occurred. Domino et al (2007) reported better performance and satisfaction outcomes using face-to-face pair programming as compared to its virtual setting. They also found that limiting the extent of collaboration can be effective, especially when programmers are more experienced.…”
Section: Literature Reviewmentioning
confidence: 98%
“…A traditional form of pair programming based on the driver-navigator model has been successful in many introductory computer science courses. Its success is noticeable in better performance in computer science assignments, increased team work in and outside class, enhanced learning, and decreased frustration (Cliburn, 2003;Domino, Collins, & Hevner, 2007;McDowell, Werner, Bullock, & Fernald, 2002;Nagappan et al, 2003;Sfetsos, Stamelos, Angelis, & Deligiannis, 2009;Thomas, Ratcliffe, & Robertson, 2003;VanDeGrift, 2004;Williams & Kessler, 2003;Williams, Yang, Wiebe, Ferzli, & Miller, 2002). However, pair programming has its weaknesses too (Bevan, Werner, & McDowell, 2002, Cliburn, 2003VanDeGrift, 2004).…”
mentioning
confidence: 99%
“…Essentially, the observer reviews the work for possible defects, writes down notes, or defines strategies for solving any issue that can arise in the task that they are working on. Various empirical studies that report beneficial effects of the use of this practice have been conducted [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Some beneficial effects reported in these studies are that pair programming helps to produce shorter programs and achieve better designs; programs contain fewer defects than do those written individually, and pairs usually require less time to complete a task than do programmers working individually.…”
Section: Introductionmentioning
confidence: 99%
“…The navigator is expected to detect errors made by the driver and offer ideas in solving problems. Pair programming, first used in 1999 as one of the core practices in the Extreme Programming (XP) software development methodology in industry, has been widely implemented in industry as well as in educational settings [2,3]. Particularly in educational settings, researchers and academics had previously applied pair programming techniques in the fields of software engineering (SE) and computer science (CS).…”
Section: Introductionmentioning
confidence: 99%